2019
DOI: 10.5194/isprs-annals-iv-2-w7-25-2019
|View full text |Cite
|
Sign up to set email alerts
|

A Many-to-Many Fully Convolutional Recurrent Network for Multitemporal Crop Recognition

Abstract: <p><strong>Abstract.</strong> Recently, recurrent neural networks have been proposed for crop mapping from multitemporal remote sensing data. Most of these proposals have been designed and tested in temperate regions, where a single harvest per season is the rule. In tropical regions, the favorable climate and local agricultural practices, such as crop rotation, result in more complex spatio-temporal dynamics, where the single harvest per season assumption does not hold. In this context, a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Two sequences of the Campo Verde database are considered: 1. from October 2015 to February 2016; and 2. from March to July 2016. The proposed methodology achieves a f 1 score of 75.89%, which is higher than the previous results reported in the literature [20,[30][31][32][33][34]. Indeed, a competitive rise of the classification rate in contrast to benchmark-and-recent works conducting experiments on the same dataset was accomplished.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Two sequences of the Campo Verde database are considered: 1. from October 2015 to February 2016; and 2. from March to July 2016. The proposed methodology achieves a f 1 score of 75.89%, which is higher than the previous results reported in the literature [20,[30][31][32][33][34]. Indeed, a competitive rise of the classification rate in contrast to benchmark-and-recent works conducting experiments on the same dataset was accomplished.…”
Section: Introductionmentioning
confidence: 55%
“…As a result, it was observed that the accuracy was better when using DL techniques (specifically, CNN), rather than the other considered methods-indeed, the CNN-based approach showed a more stable behavior. The research presented in [33,34] apply DL techniques to classify not only Campo Verde but also Luis Eduardo database [45] (another agriculture database from Brazil). Both works use approaches based on an FCN and similar parameters including a 32 × 32 patch size and assess the methodology over individual images and sequences composed by several images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The data available on the LEM benchmark database is being used in the development of PhD thesis, master dissertations, and other studies, resulting in six publications so far (Sanches et al, 2018a;Achanccaray, 2019;Chamorro, 2019;Chamorro et al, 2019, Dutra et al, 2019Prudente et al, 2019), with interesting results. And future studies are being planned to collect more data from LEM municipality regarding another Brazilian crop year and other satellites (commercial radar data) to improve the LEM database.…”
Section: Resultsmentioning
confidence: 99%
“…3.2.2 Many-to-many fully convolutional recurrent networks for multitemporal crop recognition using SAR image sequences: As stated before, tropical regions, as in the LEM database, present more complex spatio-temporal dynamics than temperate regions, where there is a single harvest per season. In this sense, Chamorro et al (2019) adapted two recurrent neural networks (RNNs), originally conceived for single harvest per season, for multidate crop recognition. In addition, a novel multidate approach based on bidirectional fully convolutional recurrent neural networks was proposed.…”
Section: Casementioning
confidence: 99%